Stanozolol and Danazol Have Different Effects on Hematopoiesis in the Murine Model of Immune-Mediated Bone Marrow Failure - Li, Hongmin; Long, Zhangbiao; Wang, Tao; Han, Bing (Frontiers in Medicine, 2021)
We conducted in vitro cell experiments to explore the direct simulation effects of stanozolol or danazol in hematopoiesis and differentiation of erythroid and megakaryocytic lines. Meanwhile, AA mouse model of lymphocyte infusion-induced bone marrow failure was built for in vivo studies. For in vitro experiment, neither stanozolol or danazol could stimulate the growth of bone marrow colonies from patients with aplastic anemia and healthy volunteers nor they can induce the erythroid and megakaryocytic differentiation of K562 cells detected by mean fluorescence intensity of CD235a or CD41. However, in the in vivo experiment, AA mice treated with cyclosporine A and danazol exhibited the most rapid recovery of platelets; the platelets count returned to normal level after three weeks of treatment, which was at least one week earlier than that in the other groups. In contrast, mice treated with cyclosporin A and stanozolol exhibited the highest hemoglobin level at the end of treatment (P<0.05). Bone marrow colony assays at 30 days showed that the number of burst-forming units-erythroid was the highest in mice treated with cyclosporin A and stanozolol, while the number of colony-forming units-granulocyte and macrophage was the highest in those treated with cyclosporin A and danazol. Compared to cyclosporin A monotherapy, additional stanozolol and danazol can both increase the level of regulatory T cells and upregulate interleukin-10, inhibiting the expression of tumor necrosis factor-α (P<0.05). However, IL-2 was more effectively reduced by danazol than by stanozolol (P<0.05). The cyclosporin A- and stanozolol-treated mice showed higher serum erythropoietin (corrected by hemoglobin level) and higher erythropoietin receptor levels in bone marrow mononuclear cells than that in the other groups (P<0.05). Conclusions: Neither stanozolol nor danazol directly stimulated hematopoiesis in vitro. However, in vivo, stanozolol may exhibit an advantage in improving erythropoiesis, while danazol may induce stronger effects on platelets . Both danazol and stanozolol exhibited immunosuppressive roles. Stanozolol could enhance the secretion of erythropoietin and expression of erythropoietin receptor on the bone marrow mononuclear cells.